Disability after encephalitis : development and validation of a new outcome score. - Lewthwaite, Penny; Begum, Ashia; Ooi, Mong How; Faragher, Brian; Lai, Boon Foo; Sandaradura, Indunil; Mohan, Anand; Mandhan, Gaurav; Meharwade, Pratibha; Subhashini, S; Abhishek, Gulia; Begum, Asma; et al. (Research, 2010)
Objective : To develop a simple tool for assessing the severity of disability resulting from Japanese encephalitis and whether, as a result, a child is likely to be dependent.